Efektifitas Permainan Congklak Pada Perkembangan Sosial Emosional Anak Usia 4-6 Tahun - RUKMINI RUKMINI (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
The social-emotional development of children aged 0-6 years is very important to be considered from an early age because it will affect social skills, now it is the same trend throughout the world. The right game can be used to stimulate optimal social-emotional development (Susanto, A., 2011). This study aimed to analyze the effectiveness of the Congklak game on the social and emotional development of children aged 4-6 years. The research design used a single group, pre-experimental pre-test-post-test model. The research was carried out in Gembong Sawah Tengah Surabaya. A total of 50 children aged 4-6 years old, were selected by simple random sampling. The independent variable is the congklak game and the dependent variable is the emotional social development. The data were collected by a set of questionnaires and analyzed by a statistical Wilcoxon signed rank test at a 95% confidence level (alpha = 0.05). Social-emotional development in children 4-6 years old was higher after intervention (mean = 27.64) than before intervention (mean=19,42). Bivariate analysis showed that there was a significant effect of the Congklak game on social-emotional development in children (p=0.001). Congklak games are effectively used to improve social-emotional development in children aged 4-6 years. Congklak game as an alternative to improve children's social-emotional development which is relatively easy and flexible in place and whoever the person is.